A Rasch Analysis on Students’ Ability in Structure and Written Expression Section of TOEFL Test - Anandi, Rizki Prahita (ICONELT, 2022)
TOEFL test has been used in the universities for many purposes, for instance, since 2021, Sharia Faculty has implemented this rule for graduation requirements. Therefore, Sharia International Center (SIC) has initiated TOEFL Training Batch 1 to analyse the students’ English ability since the students have never been exposed to the TOEFL test before. This research was carried out to analyze the students’ English proficiency and difficulty to answer questions in the Structure and Written Expression part of the TOEFL test so that the they will get an insight about what should they emphasize to improve their score. Approximately 24 students’ answer sheets were collected and analysed using Winstep from Rasch Measurement Model. They answered 40 questions of the section. The findings of the study showed that many of the students (more than 50%) have low level of structure and written expression skills. Meaning that they have difficulties in answering some questions in this section. The results also reported that they still have difficulty to answer questions related to complex sentences and parallelism in a sentence. All these findings can be a valuable information for both students and English lecturers. Lecturers can help the students improve their English ability or TOEFL score by analysing types of question they cannot answer and then design the classroom teaching and learning focusing more on this aspect.